Bill of Lading in Transporting Goods at Sea to Envisage an Efficiency of Export and Import Transaction - Sudarwanto, AL Sentot; Purwosutedjo, Grace Ayu (Yustisia, 2019)
This study discusses the law of transporting goods at sea by using a document of charge called Bill of Lading known in common law system is from the 16th century. The research is taken based on the empirical type by showing evidence obtained from the field then analyzed based on bibliography and theory which exists. The result of the research is that each of the international regulations studied does not describe explicitly what the rights and obligations of exporters and importers. However, the B/L contract on the back describes the rights and obligations of exporters and importers as "merchants". Then the results of research that Efficiency is achieved by reason if B/L has been published, No weight miscommunication, Parties abide by applicable legislation, Not falsely signing, Storing B/L in a safe place so as not to disappear, Consistent premises B/L not to be amended, Exporters researching weight standards of goods to be shipped according to ship type, Exporters studying freight forwarding companies in order to manage customs clearance, Selecting the right insurance company to be trusted, Paying attention to the cost of deviation for the benefit of shipping For carrier, Use safe payment method to avoid any more cost when transaction insecurity, Use Surrender B/L model to avoid loading time at loading and unloading ports, Checking documentation of payload including B/L whether complete or not to avoid arrest goods in Customs area, Conduct a container inspection to avoid leakage, and Prevent assignment to less competent workforce to handle cargo documents.